PERANCANGAN SOLAR CELL SYSTEM OFFGRID PADA DAERAH RAWAN GEMPA YANG TERDAPAT SITUS BERSEJARAH (Studi Kasus : Kawasan Candi Prambanan) - Redaksi Tim Jurnal (Energi & Kelistrikan, 2016)
Determination of Prambanan temple as a world cultural heritage implications for the nation's responsibility and obligation to protect and preserve the building in accordance with the convention set by UNESCO. The Convention, among others keep building preservation from the danger of war, physical damage because with age, and natural disasters. An earthquake with magnitude 6.3 in Yogyakarta in 2006 made Prambanan little structural damage. One of them is the fall of the temple stones. Historical sites requires electrical energy, especially light to keep the nation's inheritance of crime and vandalism. The electricity supply is particularly important given the current post-earthquake infrastructure much impaired and this is where alternative energy power plants is needed. The application of solar power technology offgrid System in the future is as a replacement or substitution in diesel fuel usage, as well as to increase the ratio of electricity. The study provides recommendations placement of solar cell three locations namely at location A (coordinates 110.491 -7.751 S E) with an area of 0.31 hectares, the location B (coordinates 110.493 -7.752 S E) with anarea of 0.06 hectares, and the location C Location C (coordinates 110.491 -7.750 S E) with an area of 0.05 hectares. Solar modules produced when dibutuhan power of 1500 Watts takes 47 modules with energy generated by 40 kWh. Based on a simulation of a computer program on the area of 100m2 takes 50 solar modules for generating electrical energy 53.56 kWh per day.